2000
DOI: 10.1086/315906
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Modulation of Malaria Morbidity and Mortality

Abstract: This review critically examines the relationship between nutritional status and malaria. The data indicate that protein-energy malnutrition is associated with greater malaria morbidity and mortality in humans. In addition, controlled trials of either vitamin A or zinc supplementation show that these nutrients can substantially reduce clinical malaria attacks. Data for iron indicate that supplementation may minimally aggravate certain malariometric indices in some settings and also strongly improve hematologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
190
3
11

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(208 citation statements)
references
References 138 publications
4
190
3
11
Order By: Relevance
“…This probably supports other observation that anti-oxidant nutrients such as vitamin E contained in red palm oil as well as protein deficient-diets (kwashiorkor) favour the growth and survival of the malarial parasites [22,23]. Indeed protein energy malnutrition is said to be associated with greater malarial morbidity and mortality [24]. Nonetheless, the influence of red palm oil and other tropical cooking oils on the survival and growth of malarial parasites has been of concern but remains contentious [10] .A possible mechanism of the role of red palm oil on malarial infection have recently been suggested by Yahya and Kadir [25].…”
Section: Discussionsupporting
confidence: 81%
“…This probably supports other observation that anti-oxidant nutrients such as vitamin E contained in red palm oil as well as protein deficient-diets (kwashiorkor) favour the growth and survival of the malarial parasites [22,23]. Indeed protein energy malnutrition is said to be associated with greater malarial morbidity and mortality [24]. Nonetheless, the influence of red palm oil and other tropical cooking oils on the survival and growth of malarial parasites has been of concern but remains contentious [10] .A possible mechanism of the role of red palm oil on malarial infection have recently been suggested by Yahya and Kadir [25].…”
Section: Discussionsupporting
confidence: 81%
“…One of these associations implicates the SLC39A8 locus, which encodes a zinc transporter protein highly up-regulated in response to primary T-cell activation, especially in the presence of low concentrations of zinc (33). Several studies and initiatives have proposed zinc supplementation as a strategy to help reduce the risk of malaria episodes (34,35), and our data implicate a gene whose action is potentiated by zinc but also clearly and robustly conditioned by host regulatory variation. The interaction implicating SLC39A8 illustrates a robust in vivo genotype-by-infection effect that is directly linked to the key process of T-cell development.…”
Section: Discussionmentioning
confidence: 57%
“…There is experimental evidence that vitamin A supplementation in children is associated with a reduction from 23 to 30% in mortality risk and attenuation in disease severity (59) There is also a general consensus that PEM is associated with greater malaria morbidity and mortality in humans (65). Supporting this observation, controlled clinical trials of either vitamin A or zinc supplementation indicated that these nutrients can substantially reduce clinical malaria outbreaks (66,67).…”
Section: Malnutrition Increases Risk Of Infectionmentioning
confidence: 99%